Equity in Career Development of High School Students in South Korea: The Role of School Career Education - Youngsun Lee; Gayeong Lee; Junghyun Kim; Minwook Lee (MDPI AG, 2021)
Along with the rising concerns of career education in school, the government in South Korea has increased investments for closing the opportunity gap in career education. However, limited studies explored the equity in students' outcomes of career education. Focusing on career development competencies, we examined if school career education could reduce the socio-economic disparities in the career development of high school students. We used the ordinary least squares (OLS) regression applying school-fixed effects with the representative data from the Korean Education and Employment Panel II. Findings showed that parental education level was positively linked to career development competencies of high school students, though household income was not shown as statistically significant. We also found that for students who engaged in career and vocational classes in school, the parental education level was less likely to be related to their career development competencies. Also, students who were more satisfied with school career education showed a weaker relationship between career development competencies and parental education level. Based on these findings, we discussed the role of school-based career education to narrow the gap in students' career development from socio-economic backgrounds.